Wacana Identitas Disabilitas dalam Film What They Don’t Talk When They Talk about Love (2013) - Izza Fidaul Jihad (Jurnal Media dan Komunikasi, 2020)
This study is a film text analysis study that aims to describe the disability discourse in the film What They Don't Talk When They Talk About Love (2013), which is represented and distributed to the audience regarding disability identity discourse in Indonesia today. This research is significant because of the representation of people with disabilities rarely shown as a figure and central issue. The film What They Don't Talk When They Talk About Love (2013) is a film directed by Mouly Surya that raises the big theme of the life of a person with a disability that is rarely shown primarily in presenting representations of people with disabilities that are humanist. This research method is a qualitative text-based analysis using film discourse interpretation by Jenna Wildfeuer to uncover the discourse of identity of disability in the film by doing two stages to understand and construct the meaning of the film namely the formal description of the inference process and functional analysis of the communicative purposes. The results of this study indicate that identity of disability in this film is through social interaction as something that is not bodily, but an environment that is not inclusive or discourse on the limited access of persons with hearing impairments communicating in society, through social relations persons with disabilities are shown as sexual beings and empowered over his body or discourse on sexuality and the exploration of the body of persons with disabilities, and through character representations that exist in the community or depictions of stories encountered in daily life.